TRADISI KAWIN BOYONG PADA PERKAWINAN ADAT DI DUSUN BEDAHAN, PRINGAMBA KECAMATAN PANDANARUM KABUPATEN BANJARNEGARA - Ihwan Fahidin; mutho'am muth'oam (Hukum Keluarga Islam, 2022)
Boyong marriage is a marriage carried out before the Ijab Qabul, where the groom moves to the bride's house. The procession is carried out at night, some during the day and in the evening, when the groom will move to the bride's house. Usually there will be a discussion between the two parties regarding the Boyong Marriage, after both parties have agreed, the groom will be escorted by his family from the house to the bride's house. The community's customs related to Kawin Boyong, have become an inherent culture since the first, brought by the ancestors to be made a tradition in the community of Bedahan hamlet, Pringamba Village, Pandanarum District, Banjarnegara Regency. There is an assumption that if these customs are not preserved, it will cause bad luck for the local community, because customs are like culture that are very closely held as beliefs and symbols of Java in the Bedahan Village community, Pringamba Village. But on the one hand, when the marriage has not been carried out legally, the groom stays at the bride's house, fears will occur that disobedience can even lead to a relationship that is prohibited by religion. Because the time for marriage is still waiting for the day while they are already living under the same roof. How did the tradition emerge, what is the background behind its emergence? And to what extent is the implementation of boyong marriage and its limitations, so that it becomes a tradition that needs to be preserved in the community.